2024
DOI: 10.1021/jacs.3c14381
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Electrochemical Ethylene-to-Ethylene Glycol Conversion over a Multitasking Molecular Catalyst

An-Zhen Li,
Bo-Jun Yuan,
Ming Xu
et al.

Abstract: Ethylene glycol is an essential commodity chemical with high demand, which is conventionally produced via thermocatalytic oxidation of ethylene with huge fossil fuel consumption and CO 2 emission. The one-step electrochemical approach offers a sustainable route but suffers from reliance on noble metal catalysts, low activity, and mediocre selectivity. Herein, we report a one-step electrochemical oxidation of ethylene to ethylene glycol over an earth-abundant metal-based molecular catalyst, a cobalt phthalocyan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…Duan et al reported a one-step electrochemical oxidation of ethylene to EG over a cobalt phthalocyanine supported on a carbon nanotube carrier (CoPc/CNT). 47 This catalyst produced EG with a selectivity of 100% and a TOF of 1.78 min −1 at room temperature and ambient pressure. By contrast, the TOF of Pd/C and Pd DNTs was only 0.02 and 0.01 min −1 , respectively.…”
Section: Direct Oxidation Methodsmentioning
confidence: 99%
“…Duan et al reported a one-step electrochemical oxidation of ethylene to EG over a cobalt phthalocyanine supported on a carbon nanotube carrier (CoPc/CNT). 47 This catalyst produced EG with a selectivity of 100% and a TOF of 1.78 min −1 at room temperature and ambient pressure. By contrast, the TOF of Pd/C and Pd DNTs was only 0.02 and 0.01 min −1 , respectively.…”
Section: Direct Oxidation Methodsmentioning
confidence: 99%
“…In addition to the 10 reactions mentioned in Figure , several reactions are being used for the aim of lowering H 2 production costs. Propanol , and formaldehyde , are being studied as types of PRR, and monosaccharide, ethylene, ethylene glycol, , and chitin are being studied as VARs.…”
mentioning
confidence: 99%